The Mediating Role of COVID-19 Risk Perception in the Relationship between Sports Club Innovativeness and Trust: A Case Study of Martial Arts Clubs - Kadir Yağız; Beyza Gültekin; Leyla Özer (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The perception of innovativeness within sports clubs can significantly impact consumer decision-making by reducing risk. This, in turn, can foster trust between martial arts clubs and their customers. This study seeks to investigate the role of COVID-19 risk perception in mediating the relationship between sports club innovativeness and trust in martial arts clubs, specifically during the COVID-19 pandemic. Data was gathered from 249 individuals who participate in sports clubs in Ankara, the capital city of Türkiye. The hypotheses were tested using mediation analysis with the help of the Process macro. Research has demonstrated a connection between the perception of COVID-19 risk, the innovativeness of sports clubs, and the level of trust among individuals. Researchers have found that sports clubs' innovative practices reduce the perceived risk of COVID-19 among their members, thereby boosting trust in martial arts clubs. The result of the study has important implications for sports club managers during times of crisis, such as the COVID-19 pandemic. It suggests that prioritising firm innovativeness can be a crucial strategy to influence sports consumers' trust in sports clubs.